2015
DOI: 10.1016/j.febslet.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Mir‐302c mediates influenza A virus‐induced IFNβ expression by targeting NF‐κB inducing kinase

Abstract: a b s t r a c tLittle is known about the role of microRNA during influenza A virus (IAV) infection. We observed that NIK 3 0 UTR luciferase activity was elevated during IAV infection. Further studies demonstrated that miR-302c reduced NIK expression, resulting in the reduction of IFNb mRNA expression. We found that miR-302c prevented the translocation of NF-jB from the cytosol to the nucleus. Furthermore, IAV infection downregulated miR-302c expression, leading to the activation of IFNb expression and the inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 29 publications
3
31
0
1
Order By: Relevance
“…Many viruses and viral proteins adopt microRNA mediated regulation of anti-viral pathways to alleviate their pathogenesis. Influenza A virus utilizes miR-302c to target NF-κB kinase activity in order to modulate IFN-β pathway20. Hepatitis B virus X protein has been reported to induce the expression of miR-21 to promote hepatocellular carcinoma in hepatocytes21.…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses and viral proteins adopt microRNA mediated regulation of anti-viral pathways to alleviate their pathogenesis. Influenza A virus utilizes miR-302c to target NF-κB kinase activity in order to modulate IFN-β pathway20. Hepatitis B virus X protein has been reported to induce the expression of miR-21 to promote hepatocellular carcinoma in hepatocytes21.…”
Section: Discussionmentioning
confidence: 99%
“…Previous evidence has demonstrated that several miRNAs, including miR‐33a, miR‐302c, and miR‐let‐7c, are involved in the replication of IAV . It has also been shown that miR‐146a is induced via a wide range of viral infections, and probably miR‐146a contributes to virus replication.…”
Section: Mir‐146a In Influenzamentioning
confidence: 99%
“…50 Previous evidence has demonstrated that several miRNAs, including miR-33a, miR-302c, and miR-let-7c, are involved in the replication of IAV. [99][100][101] It has also been shown that miR-146a is induced via a wide range of viral infections, and probably miR-146a contributes to virus replication. However, studies on the involvement of miR-146a in IAV infection are insufficient, and the related underlying molecular mechanisms of influenza infectious cycle remain unknown.…”
Section: Mir-146a In Influenzamentioning
confidence: 99%
“…Western blotting analyses were described in a previous study (34). Briefly, cells were harvested by low-speed centrifugation and washed with PBS.…”
Section: Western Blot Analysismentioning
confidence: 99%